2009
DOI: 10.1002/ejoc.200900586
|View full text |Cite
|
Sign up to set email alerts
|

Switching the Regioselectivity of Direct C–H Arylation of 1,3‐Dimethyluracil

Abstract: An interesting dichotomy in the regioselectivity and mechanism of direct C–H arylation of 1,3‐dimethyluracil was observed. Its Pd‐catalyzed reactions with diverse aryl halides in the absence of CuI lead preferentially to 5‐aryluracils, while reactions in the presence of CuI give 6‐aryl derivatives as the major products. Cu‐mediated reactions (in the absence of a Pd catalyst) proceed with lower efficiency but give exclusively 6‐aryluracil derivatives. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…11 Direct C–H arylation, 12 acetoxylation, 13 trifluoromethylation, 14 and dimerization 15 of uracils have been reported by Pd-catalysis. In contrast, C–H alkenylation of uracils has been typically achieved using stoichiometric amounts of Pd.…”
mentioning
confidence: 99%
“…11 Direct C–H arylation, 12 acetoxylation, 13 trifluoromethylation, 14 and dimerization 15 of uracils have been reported by Pd-catalysis. In contrast, C–H alkenylation of uracils has been typically achieved using stoichiometric amounts of Pd.…”
mentioning
confidence: 99%
“…Thus, arylation in the presence of Pd(OAc) 2 and Cs 2 CO 3 mainly formed the 5-arylated uracil analogues 66 , while coupling in the presence of Pd catalyst and CuI (3 equiv.) preferentially formed the 6-arylated derivatives 67 (Scheme 22) [57,58]. Interestingly, Cu-mediated arylation in the absence of Pd catalyst gave exclusively 6-aryluracils 67 albeit in lower yields.…”
Section: Direct Activation Of C5-h or C6-h Bond In Uracils And Uramentioning
confidence: 99%
“…In order to prepare the unprotected uracil derivatives, these protocols were also applied to N -benzyl protected uracil derivatives. Subsequent debenzylation (e.g., 67 , R = Bn) afforded efficiently 5- or 6-aryled uracil derivatives [57,58]. The experimental results indicated that different mechanisms are involved in these diverse arylation reactions [57,58].…”
Section: Direct Activation Of C5-h or C6-h Bond In Uracils And Uramentioning
confidence: 99%
“…Pd-catalyzed and/or Cu-mediated direct C-H arylations of 1,3-dimethyluracil with diverse electron-rich aryl halides was reported in 2009. [16] Synthesis of 5-and 6-aryluracil bases based on direct C-H arylations of diverse 1,3-protected uracils was reported by Hocek et al in 2011. [17] Direct alkenylation of 4H-pyrido [1,2-a]pyrimidin-4-ones via palladium-catalyzed C-H activation was developed by Cao and co-workers.…”
mentioning
confidence: 99%
“…Ethyl acetate gave the best yield while solvents such as 1,4-dioxane, acetonitrile, and toluene afforded moderate yields of the product. NMP, DMAc, and t-amyl alcohol (t-AmOH) afforded poor results (Table 1, entries [13][14][15][16][17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%